Regulating human genomic research in Africa: why a human rights approach is a more promising conceptual framework than genomic sovereignty - Kabata, Faith; Thaldar, Donrich (Frontiers in Genetics, 2023)
This article revisits the debate on the regulation of human genomic research, with a focus on Africa. The article comprehensively examines the concept of genomic sovereignty, which was invoked mainly in the global South as a conceptual framework for state regulation of human genomic research. It demonstrates that genomic sovereignty has no utility value in human genomic research as it violates the rights of individuals and researchers. By analysing Mexico’s regulatory approach based genomic sovereignty and a divergent regulatory approach, Finland’s human genomic research framework, we show that a human rights approach is more promising as it aligns with the state obligations under the right of everyone to participate in and benefit from scientific progress and its applications in international human rights law. We conclude by recommending that African states should anchor regulation of human genomic research on a human rights framework based on the right to science.